MODERN METHODS OF EMPLOYMENT REGULATION AND MANAGEMENT MECHANISMS IN THE TOURIST SERVICES MARKET (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This article carried out economic analysis on the indicators of employment of the population in the field of tourism, the level of employment in foreign countries in the regulation and management of employment in the tourist services market. Scientific-theoretical approaches of foreign scientists were studied on the topic. Efforts have been made to reveal modern methods of ensuring employment in the tourism sector, and prospects for its application have been cited.
Keywords: population, Well-Being, know-how employment, sayohat, consumption, tourism, demand, supply, Development, country, transport, tour operator, labor market, labor resources, health, hotel, economy.